Evaluation of the Suitability of Public-Private Partnership for Kowloon East Smart City Development Project in Hong Kong - Qin, Weicong; Tariq, Salman; Zayed, Tarek (International Journal of Sustainable Construction Engineering and Technology, 2021)
Smart City has become increasingly popular around the world; Hong Kong is no exception. However, Hong Kong is currently lagging in smart city development, consequently, the government has launched a pilot project ‘Kowloon East Smart City Development’. However, due to fact that the implementation of smart solutions requires a high level of technical and managerial skills and Hong Kong’s public sector does not possess any experience in the smart city, therefore, this study investigated the suitability of public-private partnership (PPP) for the pilot project. Analytic Hierarchy Process is adopted to quantitatively assess the positive and negative impacts of PPP on the smart city project. The pairwise comparison was conducted by interviewing local experts experienced in both smart cities and PPPs. The local weighting of each positive and negative factor and likelihood measurement of alternatives were carried out. Subsequently, sensitivity analysis is administrated to identify the critical factor that can affect the final decision. The results indicated that the PPP is a suitable approach for the pilot project. ‘Greater benefit to the public’ is found to be the most critical factor.